Loss of Renal Peritubular Capillaries in Hypertensive Patients Is Detectable by Urinary Endothelial Microparticle Levels. Issue 5 (November 2018) - Sun, In O; Santelli, Adrian; Abumoawad, Abdelrhman; Eirin, Alfonso; Ferguson, Christopher M.; Woollard, John R.; Lerman, Amir; Textor, Stephen C.; Puranik, Amrutesh S.; Lerman, Lilach O.
Abstract : Hypertension, an important cause of chronic kidney disease, is characterized by peritubular capillary (PTC) loss. Circulating levels of endothelial microparticles (EMPs) reflect systemic endothelial injury. We hypothesized that systemic and urinary PTC-EMPs levels would reflect renal microvascular injury in hypertensive patients. We prospectively measured by flow cytometry renal vein, inferior vena cava, and urinary levels of EMPs in essential (n=14) and renovascular (RVH; n=24) hypertensive patients and compared them with peripheral blood and urinary levels in healthy volunteers (n=14). PTC-EMPs were identified as urinary exosomes positive for the PTC marker plasmalemmal-vesicle–associated protein. In 7 RVH patients, PTC and fibrosis were also quantified in renal biopsy, and in 18 RVH patients, PTC-EMPs were measured again 3 months after continued medical therapy with or without stenting (n=9 each). Renal vein and systemic PTC-EMPs levels were not different among the groups, whereas their urinary levels were elevated in both RVH and essential hypertension versus healthy volunteers (56.8%±12.7% and 62.8%±10.7% versus 34.0%±17.8%; both P ⩽0.001). Urinary PTC-EMPs levels correlated directly with blood pressure and inversely with estimated glomerular filtration rate. Furthermore, in RVH, urinary PTC-EMPs levels correlated directly with stenotic kidney hypoxia, histological PTC count, and fibrosis and inversely with cortical perfusion. Three months after treatment, the change in urinary PTC-EMPs levels correlated inversely with a change in renal function ( r =−0.582; P =0.011). Therefore, urinary PTC-EMPs levels are increased in hypertensive patients and may reflect renal microcirculation injury, whereas systemic PTC-EMPs levels are unchanged. Urinary PTC-EMPs may be useful as novel biomarkers of intrarenal capillary loss.